Preparation method of ganoderma lucidum bitter-inhibiting and taste-masking microcapsule

By dropping the Ganoderma lucidum water extract and sodium alginate solution into the chitosan solution, Ganoderma lucidum bitter masking microcapsules with a "white-inclusive black" core-shell structure were prepared, which solved the problem of poor bitter masking of Ganoderma lucidum in the prior art, and achieved high encapsulation rate and stable quality effects.

CN119857084AActive Publication Date: 2025-04-22SICHUAN ACAD OF CHINESE MEDICINE SCI

Patent Information

Application Number
CN202510350877.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

Existing Ganoderma lucidum capsules cannot effectively mask the bitter taste of Ganoderma lucidum, and are not suitable for people such as the frail elderly, dysphagia, and patients with gastrointestinal diseases.

Method used

Ganoderma lucidum water extract and sodium alginate solution were used to drop into the chitosan solution at the same time. Through specific processes and process parameters, Ganoderma lucidum bitter-proof and taste-proof microcapsules with "white-in-black" core-shell structure were prepared.

Benefits of technology

It achieves a high encapsulation rate, effectively masks the bitter taste of Ganoderma lucidum, has low particle size and dispersion coefficient, and is stable in quality, making it suitable for a wide range of people.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857084A_ABST
    Figure CN119857084A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of pharmaceutical preparations, and particularly discloses a preparation method of a ganoderma lucidum bitter-inhibiting and taste-masking microcapsule, and the ganoderma lucidum bitter-inhibiting and taste-masking microcapsule is prepared from the following raw and auxiliary materials in parts by weight: 1 part of ganoderma lucidum water extract, 2.5-7.5 parts of chitosan solution and 2.5-7.5 parts of sodium alginate solution. According to the invention, the ganoderma lucidum water extract and the sodium alginate solution are respectively and simultaneously dripped into the chitosan solution, the ganoderma lucidum bitter-inhibiting and taste-masking microcapsule prepared by matching the specific process and corresponding process parameters has an obvious'white-in-black 'core-shell structure, the ganoderma lucidum water extract serving as a core material is successfully embedded by the gelatinized chitosan-sodium alginate serving as a wall material, and the ganoderma lucidum bitter-inhibiting and taste-masking microcapsule can be used for preparing the bitter-inhibiting and taste-masking microcapsule. The bitter taste of the lucid ganoderma can be effectively covered, the particle size and dispersion coefficient are low, the quality is stable, and the method has practical popularization and application values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and in particular relates to a method for preparing ganoderma lucidum bitterness-inhibiting and taste-masking microcapsules. Background Art

[0002] Lingzhi is a precious medicinal fungus with a mild nature and sweet taste. It is good for the heart, lung, liver and kidney meridians. Modern pharmaceutical research shows that Lingzhi is rich in polysaccharides, oligosaccharides, amino acids, proteins, steroids, alkaloids, etc. It has the effects of enhancing immunity, anti-tumor, regulating blood sugar and blood lipids, protecting the liver and detoxifying, improving sleep, and delaying aging. It has been used to treat a variety of diseases in traditional Chinese medicine for more than 2,000 years.

[0003] Ganoderma lucidum itself tastes slightly bitter, and this bitterness mainly comes from its triterpenoid compounds and other ingredients, which are also important substances for Ganoderma lucidum to exert its medicinal value. However, the bitterness of Ganoderma lucidum will affect the acceptance of the target audience, and some consumers will give up using Ganoderma lucidum products because of the bitterness. Therefore, in order to improve the acceptance of Ganoderma lucidum, Ganoderma lucidum powder is currently filled into capsules to cover up the bitterness of Ganoderma lucidum. This capsule is not suitable for the frail elderly, people with dysphagia, patients with gastrointestinal diseases, etc. In order to expand the audience of Ganoderma lucidum, it is necessary to provide a modern preparation that can both cover up the bitterness of Ganoderma lucidum and be easy to swallow. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing Ganoderma lucidum bitterness-inhibiting and taste-masking microcapsules, comprising the following steps: 1) Weigh the raw materials and auxiliary materials according to the proportion; the weight parts of the raw materials and auxiliary materials are: 1 part of Ganoderma lucidum water extract, 2.5-7.5 parts of chitosan solution, and 2.5-7.5 parts of sodium alginate solution; 2) Stir the chitosan solution and simultaneously drop the sodium alginate solution and the ganoderma lucidum water extract into the solution. Continue stirring after the addition is complete, homogenize, and dry to obtain the solution. The chitosan solution is an acetic acid aqueous solution containing chitosan; The sodium alginate solution is an aqueous solution containing sodium alginate.

[0005] Furthermore, the weight parts of the raw materials are: 1 part of Ganoderma lucidum water extract, 7.5 parts of chitosan solution, and 7.5 parts of sodium alginate solution.

[0006] Furthermore, the concentration of the Ganoderma lucidum water extract is 0.1-0.8 g crude drug / mL, preferably 0.1 g crude drug / mL.

[0007] Furthermore, the chitosan solution is an acetic acid aqueous solution containing chitosan; the chitosan concentration in the acetic acid aqueous solution is 1-3 mg / mL, preferably 2 mg / mL, and the acetic acid concentration is 0.5-1.5%, preferably 1%.

[0008] Furthermore, the concentration of the sodium alginate solution is 0.5-1.5 mg / mL, preferably 1 mg / mL.

[0009] Furthermore, in step 2), the stirring speed of the chitosan solution is 400-800 rpm, preferably 600 rpm.

[0010] Furthermore, in step 2), the stirring is continued at a temperature of 65-85° C., a speed of 100-300 rpm, and a time of 20-40 min, preferably at a temperature of 70° C., a speed of 200 rpm, and a time of 30 min.

[0011] Furthermore, in step 2), the homogenization temperature is 50-60° C., the speed is 3000-5000 rpm, and the time is 3-7 min.

[0012] Furthermore, the drying in step 2) is spray drying at a temperature of 150-200°C, preferably 170°C.

[0013] The "microcapsule" described in the present invention is a microstructure composed of wall material and core material.

[0014] The ganoderma lucidum bitter-suppressing and taste-masking microcapsules prepared by the present invention are prepared by dropping a ganoderma lucidum water extract and a sodium alginate solution into a chitosan solution respectively at the same time. The microcapsules have an obvious "white-wrapped black" core-shell structure, and the ganoderma lucidum water extract as a core material is successfully encapsulated by the gelled chitosan-sodium alginate as a wall material, with a high encapsulation rate, which can effectively mask the bitterness of the ganoderma lucidum, and have low particle size and dispersion coefficient, stable quality, and practical promotion and application value.

[0015] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0016] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Infrared spectra of different samples; Figure 2 Scanning electron microscope morphology of microcapsules; Figure 3 Transmission electron microscopy morphology of microcapsules; Figure 4Atomic force microscope morphology images of microcapsules (a: atomic force microscope 2D image of microcapsules, b: atomic force microscope 3D image of microcapsules, c: atomic force microscope 2D image of microcapsules, d: atomic force microscope 3D image of microcapsules). DETAILED DESCRIPTION

[0018] The raw materials, reagents and equipment used in the specific embodiments of the present invention are all purchased from the market. Chitosan is provided by Shanghai Aladdin Biochemical Technology Co., Ltd., with a deacetylation degree of ≥95%, a viscosity of 100-200 mPa.s, and a molecular weight (C6H 11 NO4) n , Sodium alginate was provided by Shanghai Aladdin Biochemical Technology Co., Ltd., molecular weight (C6H7O6Na) n .

[0019] Example 1 Preparation of Ganoderma lucidum bitterness-inhibiting and taste-masking microcapsules 1. Solution preparation Ganoderma lucidum water extract: Ganoderma lucidum fruiting bodies were crushed with a powder grinder, passed through a 14-mesh sieve to obtain Ganoderma lucidum powder, and water was added at a solid-liquid ratio of 1:60 (g / mL). The mixture was soaked for 120 min, and refluxed for 180 min. The extraction was repeated 4 times. After each extraction, the mixture was filtered while hot, and the residue and filter paper were refluxed for extraction. The filtrate was combined, and heated and concentrated to obtain a Ganoderma lucidum water extract with a concentration of 0.1 g crude drug / mL. Chitosan solution: Take chitosan and dissolve it in ultrapure water containing 1% acetic acid to prepare a 2 mg / mL chitosan solution; Sodium alginate solution: Take sodium alginate and dissolve it in ultrapure water to prepare a 1 mg / mL sodium alginate solution; 2. Preparation of microcapsules Take 7.5g chitosan solution and stir it at 600rpm, and at the same time, add 1g Ganoderma lucidum water extract and 7.5g sodium alginate solution through two closely placed drop tubes at the same speed (1.6mL / min). After adding, stir at 70℃ and 200rpm for 30min, then homogenize at 55℃ and 4500rpm for 5min, and finally spray dry at 170℃ to obtain Ganoderma lucidum bitter-inhibiting and taste-masking microcapsules.

[0020] The beneficial effects of the present invention are specifically described below through test examples.

[0021] Experimental Example 1 Study on Ganoderma lucidum microcapsules for suppressing bitterness and masking taste In the early stage, a lot of research has been done on the process of suppressing bitterness and masking the taste of Ganoderma lucidum. It has been determined that microcapsules with gelled chitosan and sodium alginate as wall materials and Ganoderma lucidum water extract as core material can suppress bitterness and mask the taste. The process of achieving good encapsulation of Ganoderma lucidum water extract is: dripping Ganoderma lucidum water extract and sodium alginate solution into chitosan solution at the same time, and then homogenizing and drying. The process parameters will affect the encapsulation rate and the quality of microcapsules, so further research has been conducted on the process parameters, as follows: 1. Experimental Materials Wall material: chitosan, sodium alginate Core material: Ganoderma lucidum water extract (Ganoderma lucidum fruiting bodies are crushed with a powder grinder and passed through a 14-mesh sieve to obtain Ganoderma lucidum powder. Water is added at a solid-liquid ratio of 1:60 (g / mL), soaking time is 120 minutes, heating reflux extraction is performed for 180 minutes, and the extraction times are 4 times. After each extraction, the filter is filtered while hot, and the filter residue and filter paper are further subjected to reflux extraction. The filtrate is combined, heated and concentrated to the concentration required for the experiment. The solution concentration is calculated based on the crude drug) 2 Solution preparation Chitosan solution: Chitosan was dissolved in ultrapure water containing 1%, v / v acetic acid to prepare a 2 mg / mL chitosan solution.

[0022] Sodium alginate solution: Sodium alginate was dissolved in ultrapure water to prepare a 1 mg / mL sodium alginate solution.

[0023] 3 Preparation of Ganoderma lucidum microcapsules A certain amount of 2 mg / mL chitosan solution was put into a beaker, and a 1 mg / mL sodium alginate solution of the same mass as the chitosan solution and a core material of a certain proportion to the mass of the wall material were dripped into the chitosan solution simultaneously through a peristaltic pump (1.6 mL / min) connected to two dripping tubes tightly attached, and stirred at 600 rpm. After the sodium alginate solution and the core material solution were completely dripped, they were stirred at 70 ° C and 200 rpm for 30 minutes, and then the stirred solution was homogenized at a certain homogenization temperature and speed. After the homogenization, the solid microcapsule product was obtained by spray drying.

[0024] Designed an orthogonal experiment with seven factors and three levels. 18 (3 7 ), where the last factor is a blank column (similar to the control group in a single-factor experiment). The levels and factors of the orthogonal experiment are shown in Table 1. According to the orthogonal table, a total of 18 groups of experiments were designed in this experiment, and the experimental results were statistically analyzed in turn. The obtained experimental results were analyzed using software such as orthogonal assistant or SPSS. The evaluation indicators were the encapsulation rate of Ganoderma lucidum polysaccharide and the bitterness score. The CRITIC weight method was used to perform weight analysis on the encapsulation rate of Ganoderma lucidum polysaccharide and the bitterness score.

[0025] Table 1 Orthogonal experimental factor level table Table 2 Orthogonal table L of seven-factor three-level orthogonal experiment 18 (3 7 ) 4 Analysis and testing methods 4.1 Determination of encapsulation efficiency of Ganoderma lucidum polysaccharide Weigh two portions of 0.01 g Ganoderma lucidum microcapsules, add 1 mL of ultrapure water to one portion, then centrifuge at 2000 rpm for 10 min, retain the supernatant for the determination of surface polysaccharides; add 1 mL of 29 g / L anhydrous citric acid to the other portion, and ultrasonicate for 1 h for the determination of total polysaccharides.

[0026] The encapsulation rate is calculated as follows: Encapsulation rate (%) , where W1 is the polysaccharide content on the microcapsule surface; W is the total polysaccharide content in the microcapsule.

[0027] The polysaccharide content was determined as follows: (1) Solution preparation Preparation of polysaccharide reference solution: Prepare anhydrous glucose 0.12 mg / mL aqueous solution. Accurately weigh 12 mg, i.e. 0.012 g; add ultrapure water to make up to 100 mL. Anthrone sulfate solution: Accurately weigh 0.1 g of anthrone, add 100 ml of sulfuric acid to dissolve, and shake well immediately.

[0028] (2) Preparation of standard curve Accurately measure 0.1 mL, 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, and 0.6 mL of the reference solution and place them in 10 mL stoppered test tubes respectively. Add water to 1.0 mL each. Quickly and accurately add 3 ml of anthrone sulfate solution, shake well immediately, let it stand for 15 minutes, and then immediately cool it in an ice bath for 15 minutes. Take it out, use the corresponding reagent as the blank, and measure the absorbance at a wavelength of 625 nm according to the UV-Vis spectrophotometry. Draw a standard curve with absorbance as the ordinate and concentration as the abscissa.

[0029] (3) Preparation of test solution Take the prepared sample solution and slowly add 5 mL of 95% ethanol while stirring, shake well, place at 4°C for 12 hours, centrifuge, discard the supernatant, dissolve the precipitate with hot water and transfer to a 5 mL volumetric flask, cool, add water to the mark, shake well. Take an appropriate amount of solution, centrifuge, accurately measure 1 mL of supernatant, place in a 5 mL volumetric flask, add water to the mark, shake well, and obtain.

[0030] (4) Sample measurement Accurately measure 1 mL of the test solution and place it in a 10 mL stoppered test tube. Follow the method under the standard curve preparation, starting from "rapidly and accurately add 3 mL of anthrone sulfate solution", and operate in the same way to measure the absorbance. Read the content of anhydrous glucose in the test solution from the standard curve and calculate it.

[0031] 4.2 Bitterness Evaluation Weigh 0.0125g of Ganoderma lucidum microcapsules, add 5mL of ultrapure water, and centrifuge at 2000 rpm for 15min. The supernatant is retained as the sample for sensory bitterness evaluation. Evaluation method: Sensory evaluation is based on national standards (GB / T 15038-2006) and ISO4121. The sensory evaluation adopts a 9-point system: 0 points: no bitterness; (0-2) points: slightly bitter; [2-4) points: weak bitterness; [4-6) points: obvious bitterness; [6-8] points: extremely bitter; 9 points: unbearable bitterness. Before each tasting, the evaluator rinsed his mouth with pure water, with the back surface and edge of the tongue as the main sensing area, and absorbed 0.5mL of each sample. Each sample was tasted for 10 s, and then the bitterness perception intensity of each sample was scored. After each sample was evaluated, the next sample was evaluated 5 minutes after the evaluation.

[0032] 4.3 Determination of Zeta potential and average particle size 0.010 g of Ganoderma lucidum microcapsules were weighed and added with 10 mL of ultrapure water to obtain a test sample. The Zeta potential and average particle size were measured using a Zeta potential meter and a nanoparticle size analyzer. Before the test, the sample was ultrasonicated for 5 minutes to make it evenly dispersed.

[0033] 4.4 Determination of moisture content and solubility Weigh 0.020 g of microcapsules into a crucible and dry them in an oven at 105 ºC to constant weight. Calculate the moisture content (%) of the microcapsules based on the mass loss percentage.

[0034] Weigh 0.050 (W) of microcapsules and dissolve them in 10 mL of ultrapure water. Stir at a low speed (200 rpm) on a magnetic stirrer for 15 s, then increase the speed of the magnetic stirrer to 1500 rpm and stir for another 3 min. Add the stirred sample solution to a 15 ml centrifuge tube and centrifuge at 4000 rpm for 20 min. Transfer all the sediment at the bottom of the centrifuge tube to a weighing dish (the constant weight of the weighing dish is W1), and dry it in an oven at 105 ºC to a constant weight, which is recorded as W2. Solubility (%) .

[0035] 4.5 Fourier transform infrared spectroscopy Chitosan, sodium alginate, Ganoderma lucidum water extract and Ganoderma lucidum microcapsules were tested by KBr tablet method and Fourier transform infrared spectrometer.

[0036] 4.6 Morphological Characterization A certain amount of Ganoderma lucidum microcapsule samples were taken, and the morphological characteristics of the microcapsules were observed using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and atomic force microscopy (AFM).

[0037] 5 Results 5.1 Orthogonal Experiment Results The CRITIC weight method was used to analyze the encapsulation efficiency and bitterness score of Ganoderma lucidum polysaccharide, and the weight ratio of each index was determined as follows: encapsulation efficiency 54.14%, bitterness score 45.86%, and the results are shown in Table 4. The orthogonal experimental results were comprehensively scored, and the results are shown in Table 3.

[0038] As shown in Table 3, the influence of various factors on the comprehensive score of Ganoderma lucidum microcapsules is A>B>D>F>E>C, that is, the core material concentration has the greatest influence, followed by the mass ratio of core material to wall material, while the homogenization time and homogenization speed have the smallest influence. Therefore, the optimal process for preparing Ganoderma lucidum microcapsules is A1B3C2D1E2F2, that is, the core material concentration is 0.1g / mL, the mass ratio of core material to wall material is 1:15, the homogenization speed is 4500rpm, the homogenization temperature is 55℃, the homogenization time is 5min, and the spray drying inlet air temperature is 170℃.

[0039] Table 3 Orthogonal experiment results Table 4 CRITIC weight calculation results 5.2 Process Validation According to the optimal process conditions determined by orthogonal experiment (core material concentration of 0.1g / mL, core material to wall material mass ratio of 1:15, homogenization speed of 4500rpm, homogenization temperature of 55℃, homogenization time of 5min, spray drying inlet air temperature of 170℃), three batches of microcapsules were prepared, and their Ganoderma lucidum polysaccharide encapsulation efficiency and bitterness score were measured to verify the stability of this process. The results are shown in Table 5. The results show that the Ganoderma lucidum polysaccharide encapsulation efficiency and bitterness score are the closest to the optimized process, indicating that the optimal process has good stability and the method is feasible.

[0040] Table 5 Results of encapsulation efficiency and bitterness score of Ganoderma lucidum polysaccharide in process verification experiment 5.3 Zeta potential and average particle size Zeta potential, also known as surface potential, is a representation of the amount of charge on the surface of the particle, and is related to the stability of the particle system. Zeta potential can be positive or negative. The larger the absolute value of Zeta potential, the better the stability. The Zeta potential of this Ganoderma lucidum microcapsule aqueous solution is 19.9 ± 2.17 mV, the average particle size is 3579.1 ± 148.2 d.nm, and the PDI is 0.252 ± 0.092, indicating that the microcapsules are relatively stable, can be redispersed in aqueous solution, and are not easily flocculated or precipitated due to electrostatic repulsion.

[0041] Table 6 Zeta potential and average particle size 5.4 Water content and solubility The water content of microcapsules is an important evaluation index for the storage of microcapsules. Generally speaking, the lower the water content, the longer the shelf life of the microcapsules. As shown in the table below, Ganoderma lucidum microcapsules have a low water content and good storage stability. The solubility of the microcapsules is low, presenting a suspension state.

[0042] Table 7 Water content and solubility 5.5 Fourier transform infrared spectroscopy Infrared spectrum Figure 1 As shown in the figure, first, the infrared absorption peaks of chitosan and sodium alginate are roughly the same, except that the peaks are at 3433 cm -1 Nearby is the stretching vibration peak of chitosan amino N—H, 1153 cm -1 The peak at 1416 cm is the stretching vibration peak of chitosan C—N. -1 and 1615cm -1 Nearby is the stretching vibration peak of sodium alginate -C=O-O. Secondly, the water extract of Ganoderma lucidum has a peak at 3417cm -1 、2925cm -1 、1645cm -1 、1376cm -1 、1075cm -1 There are obvious absorption peaks around 3417cm, which are attributed to carbohydrates and can provide important information about the structure of polysaccharides. -1 The strong broad band is attributed to the stretching vibration absorption peak of sugar -OH, 2925cm -1 The absorption peak belongs to the CH stretching vibration peak of the methyl or methylene in the sugar structure, 1075~1376cm -1 The absorption peak near 1645 cm is attributed to the bending vibration peak of CH, which together with the stretching vibration of CH constitutes the characteristic absorption of the sugar ring. -1The nearby absorption peak is the stretching vibration peak of C=O. The infrared spectrum of Ganoderma lucidum microcapsules also has the absorption characteristics of chitosan, sodium alginate and Ganoderma lucidum water extract, indicating that the Ganoderma lucidum water extract has been embedded in the microcapsules.

[0043] 5.6 Morphology (1) Scanning electron microscopy. Scanning electron microscopy (SEM) was used to measure the appearance of Ganoderma lucidum microcapsules. Figure 2 As shown in the figure. It can be seen that the Ganoderma lucidum microcapsules are irregular spherical, with a relatively rough surface and no cracks, indicating that the microcapsules have a good structure and can effectively protect the substances in the microcapsules. The microcapsules have a certain degree of concavity and shrinkage, which may be caused by the loss of water in the spray drying process. The particle size distribution of Ganoderma lucidum microcapsules is relatively uniform, and most of the particle sizes are distributed in the range of 0.5 ~ 5 μm. The average particle size measured by the nanoparticle size analyzer is basically consistent with the particle size measured by the scanning electron microscope.

[0044] (2) Transmission electron microscopy. Transmission electron microscopy (TEM) was used to test the morphology of Ganoderma lucidum microcapsules. Figure 3 As shown in the figure, the surface of the microcapsule is relatively rough, with an obvious "white-in-black" core-shell structure. The capsule wall tightly wraps the capsule core, the core diameter is about 0.5-2μm, and the shell thickness is about 0.1μm. This is consistent with the results of the scanning electron microscope image.

[0045] (3) Atomic force microscopy. Atomic force microscopy (AFM) was used to test the morphology of Ganoderma lucidum microcapsules. Figure 4 As shown. Figure 4 It can be seen that the surface of the microcapsules is rough and irregular in shape, with an obvious core-shell structure, and the core material is successfully embedded in the wall material, which is basically consistent with the results of scanning electron microscopy and transmission electron microscopy.

[0046] The above results show that when the core material concentration is 0.1g / mL, the mass ratio of the core material to the wall material is 1:15, the homogenization speed is 4500rpm, the homogenization temperature is 55℃, the homogenization time is 5min, and the spray drying inlet air temperature is 170℃, the encapsulation rate of Ganoderma lucidum polysaccharide in the microcapsule can reach 66.79%, and the bitterness score is 0.54 points. It can be seen that the bitterness of the Ganoderma lucidum water extract is reduced after being made into microcapsules. The average particle size is 3579.1 d.nm. The PDI and Zeta potential results show that the prepared microcapsules are relatively stable. The moisture content is 5.67%, indicating that the microcapsules have good storage stability. Infrared spectroscopy analysis confirms that the Ganoderma lucidum water extract is successfully coated with the wall material. SEM, TEM and AFM analysis show that the microcapsules are irregular spherical, with a relatively rough surface, and have an obvious "white-wrapped black" core-shell structure. The core material is successfully encapsulated by the wall material. The microencapsulation of Ganoderma lucidum water extract reduces the bitterness of the Ganoderma lucidum water extract.

[0047] 2. Comparison of Ganoderma lucidum microencapsulation technology for bitterness suppression and taste masking At present, when encapsulating drugs through the chitosan-sodium alginate gelation process, salt ions of appropriate concentration must be added to make chitosan and sodium alginate gel and successfully encapsulate drugs. However, during the encapsulation research process using Ganoderma lucidum water extract as the core material, it was found that the addition of salt ions could not gel chitosan-sodium alginate to obtain an oral preparation that could completely encapsulate Ganoderma lucidum water extract and mask its bitter taste. On this basis, a variety of Ganoderma lucidum bitterness-suppressing and taste-masking microcapsules were tried, but none of them could produce Ganoderma lucidum bitterness-suppressing and taste-masking microcapsules with good taste and stable quality. The following lists some of the processes that were attempted during the research process. The salt used in the process refers to the sodium chloride disclosed in He Dongbao et al.'s "Study on the Synergistic Interaction of Chitosan-Sodium Alginate and Its Gelation": 1. Experimental Materials Wall material: chitosan, sodium alginate, sodium chloride Core material: Ganoderma lucidum water extract (0.1g / mL, preparation method is the same as in Test Example 1) 2. Solution preparation Chitosan solution: Chitosan solution ①: Chitosan is dissolved in ultrapure water containing 1% acetic acid to prepare a 2 mg / mL chitosan solution.

[0048] Chitosan solution ②: Chitosan was dissolved in 0.15 mol / L sodium chloride solution containing 1% acetic acid to prepare a 2 mg / mL chitosan solution.

[0049] Chitosan solution ③: Chitosan was dissolved in 1.2 mol / L sodium chloride solution containing 1% acetic acid to prepare a 2 mg / mL chitosan solution.

[0050] Sodium alginate solution: Sodium alginate was dissolved in ultrapure water to prepare a 1 mg / mL sodium alginate solution.

[0051] 3 Preparation of Ganoderma lucidum microcapsules Process ①: put a certain amount of chitosan solution ① into a beaker, mix the sodium alginate solution of equal mass to the chitosan solution and the core material of 1:15 with the wall material mass, and then drip it into the chitosan solution while stirring at 600 rpm. After dripping, stir at 70°C and 200 rpm for 30 minutes, then homogenize the stirred solution at 55°C and 4500 rpm for 5 minutes. After homogenization, spray dry it at 170°C to obtain a solid microcapsule product (numbered A).

[0052] Process ②: Pour a certain amount of chitosan solution ② into a beaker, and simultaneously drop a sodium alginate solution of equal mass to the chitosan solution and a core material of a mass of 1:15 to the wall material into the chitosan solution, stirring at 600 rpm. After dropping, stir at 70°C and 200 rpm for 30 minutes, and then homogenize the stirred solution at 55°C and 4500 rpm for 5 minutes. After homogenization, spray dry at 170°C to obtain a solid Ganoderma lucidum microcapsule product (numbered B).

[0053] Process ③: a certain amount of chitosan solution ③ is filled into a beaker, and a sodium alginate solution of equal mass to the chitosan solution and a core material of a mass of 1:15 to the wall material are respectively dripped into the chitosan solution, and stirred at 600 rpm. After dripping, stir at 70°C and 200 rpm for 30 min, and then homogenize the stirred solution at 55°C and 4500 rpm for 5 min. After homogenization, spray dry at 170°C to obtain a solid Ganoderma lucidum microcapsule product (numbered C).

[0054] 4Analytical testing 4.1 Determination of encapsulation efficiency of Ganoderma lucidum polysaccharide Two portions of 0.01 g Ganoderma lucidum microcapsules were weighed, one portion was added with 1 mL of ultrapure water, and then centrifuged at 2000 rpm for 10 min. The supernatant was retained for the determination of surface polysaccharides; the other portion was added with 1 mL of 29 g / L anhydrous citric acid and ultrasonicated for 1 h for the determination of total polysaccharides.

[0055] The encapsulation rate is calculated as follows: Encapsulation rate (%) , where W1 is the polysaccharide content on the microcapsule surface; W is the total polysaccharide content in the microcapsule.

[0056] The polysaccharide content was determined as follows: (1) Solution preparation Preparation of polysaccharide reference solution: Prepare anhydrous glucose 0.12 mg / mL aqueous solution. Accurately weigh 12 mg, i.e. 0.012 g; add ultrapure water to make up to 100 mL. Anthrone sulfate solution: Accurately weigh 0.1 g of anthrone, add 100 ml of sulfuric acid to dissolve, and shake well immediately.

[0057] (2) Preparation of standard curve Accurately measure 0.1 mL, 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, and 0.6 mL of the reference solution and place them in 10 mL stoppered test tubes respectively. Add water to 1.0 mL each. Quickly and accurately add 3 ml of anthrone sulfate solution, shake well immediately, let it stand for 15 minutes, and then immediately cool it in an ice bath for 15 minutes. Take it out, use the corresponding reagent as the blank, and measure the absorbance at a wavelength of 625 nm according to the UV-Vis spectrophotometry. Draw a standard curve with absorbance as the ordinate and concentration as the abscissa.

[0058] (3) Preparation of test solution Take the sample solution prepared under "4.1 Determination of encapsulation efficiency of Ganoderma lucidum polysaccharide" and slowly add 5 mL of 95% ethanol while stirring, shake well, place at 4℃ for 12 hours, centrifuge, discard the supernatant, dissolve the precipitate with hot water and transfer to a 5 mL volumetric flask, cool, add water to the mark, and shake well. Take an appropriate amount of solution, centrifuge, accurately measure 1 mL of supernatant, place in a 5 mL volumetric flask, add water to the mark, shake well, and obtain.

[0059] (4) Sample measurement Accurately measure 1 mL of the test solution and place it in a 10 mL stoppered test tube. Follow the method under the standard curve preparation, starting from "rapidly and accurately add 3 mL of anthrone sulfate solution", and operate in the same way to measure the absorbance. Read the content of anhydrous glucose in the test solution from the standard curve and calculate it.

[0060] 4.2 Bitterness and saltiness evaluation Weigh 0.0125g of Ganoderma lucidum microcapsules, add 5mL of ultrapure water, and centrifuge at 2000 rpm for 15min. The supernatant is retained as the sample for sensory bitterness evaluation. Evaluation method: Sensory evaluation is based on national standards (GB / T 15038-2006) and ISO4121. The sensory evaluation adopts a 9-point system: 0 points: no bitterness; (0-2) points: slightly bitter; [2-4) points: weak bitterness; [4-6) points: obvious bitterness; [6-8] points: extremely bitter; 9 points: unbearable bitterness. Before each tasting, the evaluator rinsed his mouth with pure water, with the back surface and edge of the tongue as the main sensing area, and absorbed 0.5mL of each sample. Each sample was tasted for 10 s, and then the bitterness perception intensity of each sample was scored. After each sample was evaluated, the next sample was evaluated 5 minutes after the evaluation.

[0061] Since salt was added to chitosan, the sensory evaluation added saltiness evaluation, and the score level was consistent with the bitterness evaluation.

[0062] 4.3 Determination of average particle size 0.010 g of Ganoderma lucidum microcapsules were weighed and added with 10 mL of ultrapure water to obtain a test sample. The average particle size was measured using a nanoparticle size analyzer. Before the test, the sample was ultrasonicated for 5 minutes to make it evenly dispersed.

[0063] 5 Results Three batches of samples A, B and C were prepared according to the corresponding process, and the encapsulation efficiency, bitterness and saltiness scores, and particle size were measured. The results are as follows: 5.1 Encapsulation efficiency, bitterness and saltiness ratings of Ganoderma lucidum polysaccharides The encapsulation efficiency of sample A was 59.57±2.89, the bitterness score was 0.94±1.12, the encapsulation efficiency of sample B was 44.05±1.91, the bitterness score was 0.63±0.69, the saltiness score was 4.44±1.45, and the encapsulation efficiency of sample C was 0.00, the bitterness score was 0.50±0.60, and the saltiness score was 6.31±1.22. The encapsulation efficiency of Ganoderma lucidum polysaccharide of samples A, B, and C was lower than that of the sample prepared under the best process of Experimental Example 1 (66.5266.79±1.96). In addition, the bitterness score of sample A was higher than that of the sample prepared under the best process of Experimental Example 1 (0.750.54±0.27). In addition to bitterness, samples B and C could also taste salty. Although the saltiness weakened the perception of bitterness, it resulted in a poor overall taste and low acceptance in the test.

[0064] Table 8 Results of encapsulation efficiency and taste score of Ganoderma lucidum polysaccharide 5.2 Average particle size The encapsulation efficiency of sample C was 0, so the average particle size was not measured.

[0065] The polydispersity index (PDI) indicates the uniformity of the particle size distribution. The higher the PDI value, the greater the difference in particle size. The average particle size of sample A is 4178±650.1 d.nm, and the PDI is 0.321±0.275. The average particle size of sample B is 6445±1054 d.nm, and the PDI is 0.252±0.092. The average particle size and PDI of samples A and B are higher than those of the sample prepared under the optimal process of test example 1 (average particle size 3579.1±148.2 d.nm, PDI 0.252±0.092), indicating that the particles of samples A and B are relatively large, the particle size distribution is wide, and the difference is relatively large.

[0066] Table 9 Average particle size The above results show that when preparing microcapsules, after the sodium alginate solution and the ganoderma lucidum water extract are mixed, the chitosan solution is then dropped in, the ganoderma lucidum water extract cannot be well encapsulated in the wall material, and the prepared microcapsules have a stronger bitter taste, and a larger particle size and dispersion coefficient than the process in which the sodium alginate solution and the ganoderma lucidum water extract are dropped in the chitosan solution at the same time; when the sodium alginate solution and the ganoderma lucidum water extract are dropped in the chitosan solution containing salt ions at the same time, the obtained microcapsules have not only bitter but also salty taste, the overall taste is not good, the particle size is also increased, and with the increase of the salt ion concentration, the encapsulation effect of the ganoderma lucidum water extract becomes worse, which ultimately leads to the inability of chitosan-sodium alginate to form gel. It is explained that for the core material with complex ingredients such as Ganoderma lucidum water extract, only by dropping sodium alginate solution and Ganoderma lucidum water extract into chitosan solution prepared with water at the same time, can the Ganoderma lucidum water extract as the main drug also play the role of auxiliary molding, so that sodium alginate-chitosan gelation can be formed, thereby well encapsulating the Ganoderma lucidum extract in the colloid. At the same time, through the coordination of specific process parameters, the microcapsule has a high encapsulation rate, a small particle size and dispersion coefficient, stable quality, and obvious bitterness suppression and taste masking effects.

[0067] In summary, the Ganoderma lucidum bitter-suppressing and taste-masking microcapsules prepared by the present invention through the specific process and the coordination of corresponding process parameters by dropping the Ganoderma lucidum water extract and the sodium alginate solution into the chitosan solution respectively at the same time have an obvious "white-wrapped black" core-shell structure, and the Ganoderma lucidum water extract as the core material is successfully encapsulated by the gelled chitosan-sodium alginate as the wall material, with a high encapsulation rate, which can effectively mask the bitterness of Ganoderma lucidum, and has low particle size and dispersion coefficient, stable quality, and practical promotion and application value.

Claims

1. A method for preparing Ganoderma lucidum bitterness-inhibiting and taste-masking microcapsules, characterized in that: The steps include: 1) Weigh the raw materials and auxiliary materials according to the proportion; the weight parts of the raw materials and auxiliary materials are: 1 part of Ganoderma lucidum water extract, 2.5-7.5 parts of chitosan solution, and 2.5-7.5 parts of sodium alginate solution; 2) Stir the chitosan solution and simultaneously drop the sodium alginate solution and the ganoderma lucidum water extract into the solution. Continue stirring after the addition is complete, homogenize, and dry to obtain the solution. The chitosan solution is an acetic acid aqueous solution containing chitosan; The sodium alginate solution is an aqueous solution containing sodium alginate.

2. The preparation method according to claim 1, characterized in that: The weight parts of the raw materials are: 1 part of Ganoderma lucidum water extract, 7.5 parts of chitosan solution, and 7.5 parts of sodium alginate solution.

3. The preparation method according to claim 1, characterized in that: The concentration of the ganoderma lucidum water extract is 0.1-0.8 g crude drug / mL.

4. The preparation method according to claim 1, characterized in that: The chitosan concentration in the acetic acid aqueous solution is 1-3 mg / mL, and the acetic acid concentration is 0.5-1.5%.

5. The preparation method according to claim 1, characterized in that: The concentration of the sodium alginate solution is 0.5-1.5 mg / mL.

6. The preparation method according to claim 1, characterized in that: Step 2) The stirring speed of the chitosan solution is 400-800 rpm.

7. The preparation method according to claim 1, characterized in that: Step 2) The stirring is continued at a temperature of 65-85° C., a speed of 100-300 rpm, and a time of 20-40 min.

8. The preparation method according to claim 1, characterized in that: Step 2) The homogenization temperature is 50-60°C, the speed is 3000-5000 rpm, and the time is 3-7 min.

9. The preparation method according to claim 1, characterized in that: Step 2) The drying is spray drying at a temperature of 150-200°C.

Citation Information

Patent Citations

  • Method for preparing sodium alginate / chitosan sustained-release microcapsule by external gelation

    CN101239052A

  • Enrofloxacin stratified high molecular taste mashing skeleton particle and preparation method thereof

    CN105078899A

  • Method for preparing ganoderma lucidum polysaccharide microcapsule by using microfluidic technology

    CN111329066A

  • Probiotic clausena lansium microcapsule and preparation method and application thereof

    CN111602810A

  • Microcapsules and method of preparing the same

    TW200922638A

Cited By

  • Agilawood and lucid ganoderma fermented composition and preparation method thereof

    CN122229939A

  • A chrysanthemum morifolium fermented composition and a preparation method thereof

    CN122229939B